Analysis of Land Subsidence (Case Study: Kenagarian Bancah Batu Balang Kabupaten Lima Puluh Kota Road) - Elvi Syamsuir; Fatma Ira Wahyuni; Dio Dio; Ramacos Fardela (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2023)
The term land subsidence denotes the collapse of a building due to compression and deformation of the soil layer beneath the building. Settlement will occur if a layer of soil is loaded, settlement is also influenced by the distribution of soft soil or clay found below the surface on alluvial plains. In this case, the West Sumatra-Riau Jorong Bancah Kenagarian Batu Balang road, Kabupaten Lima Puluh Kota, is one of the areas traversed for the construction of the West Sumatra-Riau cross road. This road is included in the category of primary local roads with a road width of 6 m. Currently, the physical condition of the West Sumatra-Riau Jorong Bancah Kenagarian Batu Balang road, Kabupaten Lima Puluh Kota, has been repaired and some has not been repaired. The road in Bancah includes the Payakumbuh – Tanjung Pati ring road, which is used by the local community and trucks to speed up the road. Based on this, a study was carried out to determine the condition of the soil on the road. This research was conducted by taking samples at the research location and then determining the water content, specific gravity, density and finally the California Bearing Ratio (CBR). The average water content for undisturbed samples was found to be 30.98%. Based on the test results, it was found that the average soil density was 1.10 gr/cm³, so it can be concluded that the soil tested was a type of clay. Furthermore, the results of testing the soil density obtained dry specific gravity, the maximum ɤd is 2.83 t/m and the optimum moisture content is 16%. The density obtained from the results of testing in the Civil Engineering Laboratory of STT Payakumbuh is the average soil density: 2.59 gr/cm³ which is categorized as soft soil. The results of laboratory CBR testing found that the average CBR of soil was 5.27%. This shows that the land is not suitable for use for construction if the minimum standard is 6%.